'It's Fast, It's Quick, It Stops Me Being Sick': How to influence preparation of opioid tablets for injection. (10th May 2017) - Lafferty, Lise; Treloar, Carla; van Breda, Nick; Steele, Maureen; Hiley, Sarah; Flaherty, Ian; Salmon, Allison
Abstract: Introduction and Aims. Injection of pharmaceutical opioids (PO) among people who inject drugs has increased in many countries. The common method for preparing PO tablets for injection uses heat, resulting in greater particulate matter and therefore increased risk of local infection risk and damage to veins and organs. A cold preparation process has fewer risks, but this preparation method is not commonly used. This study seeks to explore how people who inject PO learn to prepare injections and how health promotion efforts could influence practice.Design and Methods. Between March and December 2013, qualitative interviews were undertaken with 33 clients of Sydney's Medically Supervised Injecting Centre who inject PO tablets regarding sources of knowledge and current preparation methods for injection of POs.Results. Overwhelmingly, the most commonly reported source of knowledge around injection of tablets was others who inject. Most participants reported heating the solution as the quickest way to administer the drug. Attitudes to the use of wheel filters varied, with some participants reporting that they would use the filters if they were shown how, while others reported a number of barriers to using filters, including complexity of use.Discussion and Conclusions. Harnessing the power of social connections may provide avenues for education about safer injecting of tablets, including the use of wheel filters. Further work is required to debunk myths about the relative potencies of cold versus hot drug solution. Collaborations between harm reduction workers and peer workers would assist in knowledge dissemination regarding safer injecting practices.